CSC253: Interactive Multimedia / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
This course will introduce the essential topics in interactive multimedia application development. It includes concepts in multimedia, basic multimedia elements such as text, graphics, audio, video, and animation also the requirements of multimedia project development using authoring tools. Besides that, the implications of data storage and retrieval methods and also the role of teamwork in multimedia project development will also be highlighted. It will also discuss on multimedia computer hardware and software, current multimedia authoring tools, file formats, media storage and memory management. Applications of multimedia for the Internet will also be emphasized.